Optimization of Turning Parameters to Minimize Production Cost using Genetic Algorithm - M. F. F., Ab Rashid; Shah, Izwandi (2009)

(untitled)
In material removal process, turning is one of the oldest processes that were introduced to remove unwanted material by rotating the workpiece. The turning process were significantly change by introduction of computer numerical control (CNC). However, the process improvement is not stopping there, but the focused has change to reduce the machining cost. The parameter setting will affects a few independent variables such as surface roughness, cutting force, machining time, machining cost and so on. Improper parameter selection will caused vibration in cutting, unsecure workpiece, unappealing finishing and cost consuming. Therefore, the optimum parameter setting is required because it related to certain quality characteristics such as the unit production cost. This paper presents the study to minimize production cost for CNC turning process by using genetic algorithm (GA) method with some modification. The result shows that, the GA with modification was capable to reduce 2.9% of production cost compare to existing GA and two other methods. Therefore the optimum parameter setting which produce minimum production cost and in acceptable quality range was established.